A oferta cultural e criativa e sua contribuição ao turismo criativo: modelo prático-teórico - Corá, Jacqueline Maria (My University, 2022)
The technological advances intensified in of the last decades of the 20th century have changed the scenario of global competition. In the context of contemporary societies, the city assumes a new centrality and, as a result, new functions. Its territory must consider meeting the demands of this urban population that is no longer aligned with those of industrial societies. In this sense, culture and creativity come to be understood as strategic resources in the economic mix of contemporary societies and, through cultural and creative industries and creative tourism, generate positive externalities that promote economic and social development. Therefore, in face of the accelerated urbanization that goes hand in hand with the phenomenon of deindustrialization that affects a large part of cities in contemporary times, the need to identify and value the practices that use culture and creativity to add value to the city, its inhabitants, and its economy, and that contribute to its sustainability, becomes evident. Thus, it is necessary to understand which are the essential aspects, here understood as dimensions, that allow us to evaluate the potential existing in a location, for the supply of cultural and creative goods and services and their contribution to tourism. Thus, based on this questioning, the objective of this study is to elaborate a Practical-Theoretical Model in order to understand a locality's potential for the supply of cultural and creative goods and services, with emphasis on creative tourism (supported by the creative economy). To this end, the study is based on the weberian comprehensive methodology, which proposes the construction of a kind of ideal type bringing together all the particularities found in phenomena of the same nature, thus obtaining an abstract and utopian model, whose main objective is to establish a confrontation with the empirically observed reality. Thus, it was adopted as a methodological procedure, besides the theoretical review, in order to sustain the constructs of this study, an exploratory research, through the content analysis of sixteen applied studies (Indexes, Monitors, Networks, ISOs, Strategic Plans). From these analyses, we proceeded to define the elements defined to integrate the Model: six Dimensions (Human, Economic, Social, Cultural, Governance, and Instrumental); sixteen categories, indicators, and variables. The complexity of the structure requires, for its operationalization, adjustments consistent with the characteristics of the place to which it will be applied and the size of the research team. [resumo fornecido pelo autor]
Os avanços tecnológicos intensificados a partir das últimas décadas do século XX alteraram o cenário da competição global. No contexto, então, das sociedades contemporâneas, a cidade assume nova centralidade e, decorrente dela, novas funções. Seu território deve considerar atender às demandas dessa população urbana que não mais se alinha as das sociedades industriais. Nesse sentido, a oferta cultural e a criativa, nas localidades, passa a ser entendida como recurso estratégico no composto econômico das sociedades contemporâneas e, por meio das indústrias culturais e criativas e do turismo criativo, gera externalidades positivas promotoras de desenvolvimento econômico e social. Portanto, diante da acelerada urbanização, par e par ao fenômeno da desindustrialização que acomete grande parte das cidades na contemporaneidade, evidencia-se a necessidade de identificar e valorizar as práticas que utilizam a cultura e a criatividade para agregar valor à cidade, aos seus habitantes e a sua economia e que contribuam para a sua sustentabilidade. Assim, é preciso compreender quais são os aspectos essenciais, aqui entendidos como dimensões, que permitem avaliar o potencial existente em uma localidade para a oferta de bens e serviços culturais e criativos e sua contribuição ao turismo. Dessa maneira, a partir desse questionamento, objetiva-se, com este estudo, elaborar um Modelo Prático-Teórico, a fim de compreender as potencialidades de uma localidade para a oferta de bens e serviços culturais e criativos, com destaque ao turismo criativo (sustentadas na economia criativa). Para tanto, o estudo está assentado na metodologia compreensiva weberiana, que propõe a construção de uma espécie tipo ideal congregando todas as particularidades encontradas em fenômenos de mesma natureza, obtendo-se, portanto, um modelo abstrato e utópico, cujo principal objetivo é estabelecer um confronto com a realidade observada empiricamente. Dessa forma, adotou-se como procedimento metodológico, além da revisão teórica, a fim de sustentar os construtos deste estudo, uma pesquisa exploratória, por meio da análise de conteúdo de 16 estudos aplicados (Índices, Monitores, Redes, ISOs, Planos Estratégicos). A partir dessas análises, procedeu-se a definição dos elementos para integrar o Modelo: seis Dimensões (Humana, Econômica, Social, Cultural, Governança e Instrumental); 16 categorias de análise, indicadores e variáveis. A complexidade da estrutura requer, para sua operacionalização, ajustes coerentes com as características do local a qual será aplicado o Modelo e ao tamanho da equipe de investigação. [resumo fornecido pelo autor]
Keywords: Turismo; Cultura; Criatividade; Tourism; Culture; Creative ability